Stakeholder perspectives on barriers and facilitators to hypertension control in urban Haiti: a qualitative study to inform a community-based hypertension management intervention - Reichling St Sauveur; Rodney Sufra; Marie Christine Jean Pierre; Joseph Inddy; Mirline Jean; Nour Mourra; Radhika Sundararajan; Margaret L. McNairy; Jean W. Pape; Vanessa Rouzier; Jessy Devieux; Lily D. Yan (BMC Public Health)
Abstract Background Uncontrolled hypertension is the leading modifiable risk factor for cardiovascular disease mortality and remains high in low-middle income countries like Haiti. Barriers and facilitators to achieving hypertension control in urban Haiti remain poorly understood. Elucidating these factors could lead to development of successful interventions. Methods We conducted semi-structured interviews with healthcare providers (10) and patients with hypertension (10) from the Haiti Cardiovascular Disease Cohort, using guides developed using the Consolidated Framework for Implementation Research. Participants were recruited using purposive sampling, and thematic content analysis was conducted in NVIVO software. Results At the individual level, barriers to hypertension control included hypertension is asymptomatic, hypertension is due to stress, difficulty changing behaviors within shared households, and fear of becoming dependent on medications. Facilitators included spiritual faith in doctors, high awareness of diet and exercise, belief in medication effectiveness, and family as motivation to treat hypertension. At the inner setting clinic level, barriers included limited physician–patient time during visits, residual stigma around cardiovascular services located on same campus as HIV care, and patient preference for physician guidance. Facilitators included patients treated with respect at clinic, and strong provider-patient rapport. At the outer setting societal level, only barriers were mentioned, including extreme poverty, civil insecurity, and stress making hypertension worse. Conclusions These findings can inform the development of future efforts to design interventions to improve hypertension control in Haiti.